Mobile navigation system using GPS / Salmi Abd Wahab - Abd Wahab, Salmi (2006)
This thesis is about Navigation System Using GPS in which to conduct comparative study on different GPS platforms on Windows Mobile 5 PDA, Palm OS PDA, notebook and GPS60CS and to evaluate user acceptance of replacing paper-based map with the digital map based on effectiveness, ease of use and efficiency. Traditionally, people use paper-based map as the only navigation tool despite the drawbacks such as people find it difficult to locate themselves in an unfamiliar area, map will not be updated frequently and they tend to getting lost while traveling. Therefore, the Navigation System Using GPS on four different platforms are presented as the solution to this problem. As for the methodology, several phases are involved such as data collection, planning, analysis, design, installation and configuration and finally testing. As for the testing, 20 respondents were involved in using the both paper-based map and digital map. For paper-based map use, only two of them managed to reach the destination. For digital map using GPS on the other hand, all respondents managed to reach the destination. From the questionnaire provided, it was found that all respondents prefer digital map to paper-based map and they stated that the digital; map is more practical, effective and easy to handle. From this result, we can conclude that digital map is plausible to replace paper-based map in which Windows Mobile PDA with GPS is the most suitable for normal use and GPS60CS for adventurous use.